The benefits and limits of computerization in conflict simulation. - Sabin, Philip (Literary & Linguistic Computing, 2011)
Computing is not the only way to model and simulate humanities problems. In the specific field of conflict simulation, there is a long and continuing tradition of using manual modelling techniques such as maps and counters to create playable games which mirror some of the dynamics of real armed conflicts. Computer games are not automatically superior to such manual models, since mass market commercial software focuses far more on entertainment than on realistic simulation, and since the enormous capabilities of computers tend to encourage detailed incorporation of quantifiable technicalities at the expense of the vital but much less tractable human element. The biggest limitation of computer models is their limited transparency and design accessibility for non-programmers such as humanities students and scholars. Manual modelling offers a valuable ‘bridge’ between computing and traditional humanities scholarship, allowing easier generation and use of specifically tailored models, and building synergistic relationships which foster more widespread and effective adoption of digital techniques.